2004
DOI: 10.1111/j.0435-3676.2004.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐magnitude/low‐frequency fluvial events generated by intense snowmelt or heavy rainfall in arctic periglacial environments in northern swedish lapland and northern siberia

Abstract: In the Latnjavagge drainage basin (68°21′N, 18°29′E), an arctic‐oceanic periglacial environment in northernmost Swedish Lapland, the fluvial sediment transport and the characteristics and importance of high‐magnitude/low‐frequency fluvial events generated by intense snowmelt or heavy rainfall have been investigated and compared with snowmelt‐ and rainfall‐induced discharge peaks in the Levinson‐Lessing Lake basin (Krasnaya river system) on the Taimyr Peninsula, an arctic periglacial environment in northern Sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 13 publications
3
53
0
Order By: Relevance
“…Hence, this research indicates that sediment storage remains an important process five years after catchment disturbance. These results are broadly consistent with studies in other regions where catchment perturbations that cause increased sediment availability are buffered through channel storage processes (e.g., Beylich and Gintz, 2004;Beylich and Sandberg, 2005). In combination with a reduced period of sediment transport during snowmelt high flow conditions caused by channel snow pack, the Arctic fluvial system appears to be effective at dampening the downstream fluvial impact of catchment disturbance in a manner consistent with other settings.…”
Section: Seasonal Sediment Dynamics In a High Arctic Riversupporting
confidence: 90%
“…Hence, this research indicates that sediment storage remains an important process five years after catchment disturbance. These results are broadly consistent with studies in other regions where catchment perturbations that cause increased sediment availability are buffered through channel storage processes (e.g., Beylich and Gintz, 2004;Beylich and Sandberg, 2005). In combination with a reduced period of sediment transport during snowmelt high flow conditions caused by channel snow pack, the Arctic fluvial system appears to be effective at dampening the downstream fluvial impact of catchment disturbance in a manner consistent with other settings.…”
Section: Seasonal Sediment Dynamics In a High Arctic Riversupporting
confidence: 90%
“…Most of it has been eroded along and close to the riverbanks. It can be concluded that it is mainly the rapid mass-wasting processes that transport sediments along all of the cascading systems (Jonasson and Nyberg 1999;Jonasson et al 2002;Beylich and Gintz 2004).…”
Section: Research Activities Geomorphological Studiesmentioning
confidence: 99%
“…Ongoing hydrological monitoring has shown the importance of high magnitude/low frequency discharge events (Gude et al 2000;Beylich and Gintz 2004), in particular during summer and autumn rainstorms. At two occasions during the last decades, some of the rivers affected by rainstorms have carried suspended sediments in 1 or 2 h that normally require several years to be transported (Jonasson and Nyberg 1999).…”
Section: Research Activities Geomorphological Studiesmentioning
confidence: 99%
“…Translation slides 11. Deflation With respect to the temporal variability of process intensities and/or process frequencies the main snow melt period (late May -June/July) which is characterised by high runoff, increased fluvial transport, slush flow activity, ground avalanches and rock and boulder falls as well as August which is the month showing the highest frequency of extreme rainfall events (Beylich, 2003;Beylich & Gintz, 2004) triggering debris flows, translation slides, secondary rock falls, boulder falls, peak runoff and increased fluvial transport, can be pointed out as periods with comparably high activity. The period from late October until early May is compared to that characterised by only very little (single avalanches) or no activity (Beylich et al, 2006b;Beylich, 2008 (Beylich & Sandberg, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Stable freezing temperatures with little daily fluctuation at 10 cm above ground and autumn snow accumulation usually occur from September/October onwards. Regarding the summer months June -August, August shows the highest mean precipitation (82 mm) and also the highest frequency of extreme rainfall events (Beylich, 2003;Beylich & Gintz, 2004). Precipitation from June to August accounts for about one quarter of the mean annual precipitation.…”
Section: Study Areasmentioning
confidence: 99%